World's Largest Ships
On recto: Imperator 919 ft. long 52,000 tons Vaterland 950 ft. long 58,000 tons In regular service to London, Paris, Hamburg Cruises to the Land of the Midnight Sun during June, July, and August from Hamburg Grand Cruise Around the World and through the Panama Canal by S.S. Cleveland, January 31, 1915 reaching San Francisco at the opening of the Panama Pacific Exposition Duration 135 days Cost $900 up Our Tourist Department arranges tours to all parts of the world, furnishes tickets and takes care of all travel detail Write for full information Hamburg-American Line 41-45 Broadway, N.Y. Philadelphia, New Orleans,Boston.Minneapolis,Baltimore,St. Louis, Pittsburgh, Montreal. Chicago, San Francisco.